INTRODUCTION. EVOLUTION, BIOGEOGRAPHY AND SYSTEMATICS OF THE APIALES (ARALIACEAE AND APIACEAE) - WATSON, M. F.; PLUNKETT, G. M.; DOWNIE, S. R.; LOWRY II, P. P. (Edinburgh Journal of Botany, 2001)
The family Apiaceae (Umbelliferae) can be credited with two major landmarks in botanical history: the first systematic monographic treatment of any plant group (Morison, 1672), and the first international symposium dedicated to systematic research on a plant family (Heywood, 1971). The 1970 symposium on the Biology and Chemistry of the Umbelliferae held at the University of Reading, UK, resulted from the large body of research interest in the family around the world at that time, and helped to stimulate further work on the Apiaceae. It also provided a model for similar symposia on major plant groups in the years to follow, including Asteraceae (Heywood et al., 1977), Brassicaceae (Vaughan et al., 1976), Lamiaceae (Harley & Reynolds, 1992), Solanaceae (Hawkes et al., 1979), and Fabaceae (Summerfield & Bunting, 1980; Polhill & Raven, 1981). Growing interest in umbellifers soon resulted in a second international symposium on the family held at the Centre Universitaire de Perpignan, France, in 1977 (Cauwet-Marc & Carbonnier, 1982). Although a large role of this second symposium was to review progress on a major co-operative research programme focused mainly on the tribe Caucalideae, participants with other interests were also involved, and wider developments in the systematics of the family were discussed.